2007
DOI: 10.1007/s10461-007-9312-x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use, Depressive Symptoms and the Receipt of Antiretroviral Therapy in Southwest Uganda

Abstract: Alcohol use and depressive symptoms are associated with reduced access to antiretroviral therapy (ART) in the developed world. Whether alcohol use and depressive symptoms limit access to ART in resource-limited settings is unknown. This cross-sectional study examined the association between alcohol use, depressive symptoms and the receipt of ART among randomly selected HIVpositive persons presenting for primary health care services at an outpatient HIV clinic in Uganda. Depressive symptoms were defined by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
72
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 32 publications
(29 reference statements)
4
72
2
Order By: Relevance
“…Thirty relevant studies were identified, of which 11 were in peerreviewed journals [15][16][17][18][19][20][21][22][23][24][25] and 19 were in conference abstracts. [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] The earliest studies included in this review were from 2004, reflecting a greater emphasis on research in this field after major initiatives were undertaken (such as ''3 by 5'' by the WHO and the President's Emergency Plan for AIDS Relief [PEPFAR]) to increase ART access in resource-limited countries.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirty relevant studies were identified, of which 11 were in peerreviewed journals [15][16][17][18][19][20][21][22][23][24][25] and 19 were in conference abstracts. [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] The earliest studies included in this review were from 2004, reflecting a greater emphasis on research in this field after major initiatives were undertaken (such as ''3 by 5'' by the WHO and the President's Emergency Plan for AIDS Relief [PEPFAR]) to increase ART access in resource-limited countries.…”
Section: Resultsmentioning
confidence: 99%
“…[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] The earliest studies included in this review were from 2004, reflecting a greater emphasis on research in this field after major initiatives were undertaken (such as ''3 by 5'' by the WHO and the President's Emergency Plan for AIDS Relief [PEPFAR]) to increase ART access in resource-limited countries. Among the 30 studies, 21 were from Africa,* 6 from east/southeast Asia,The data collection methods described in the papers comprised mostly of interviews (22 studies), y surveys (7 studies), 16,27,29,34,39,40,42 review of clinical data (7 studies), 18,20,22,27,31,36,38 and focus-group discussions (6 studies). 21,23,28,32,42,43 Respondents included PLWHA with/without ART (22 studies), z noninfected people including elders, teenagers, and university students (11 studies), § health care workers including nurses, doctors, social workers, laboratory technologists (7 studies), 15,21,25,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies carried out in Sub-Saharan Africa reflect a high prevalence. Closer home, a study at a Ugandan university teaching hospital found the prevalence of alcohol use disorders at 12% (Martinez P. et al, 2008) while one in Ethiopia found the prevalence at 32% (Soboka M. et al, 2014).…”
Section: Issn: 2320-5407mentioning
confidence: 99%